PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA E-COMMERCE LAZADA DI KOTA BATAM: Product quality; promotion; Buying decision - SIGARLAKI, REYVI FLANNY; surhadi (LPPM Universitas Putera Batam, 2024)
The impact of changes from one era to another, we know that technology and information have become a need for people in all corners of the world, with this we can see the birth of many online buying and selling business opportunities or online applications that have been created which many people call Marketplaces, there are The 10 market places with the highest number of visitors in Indonesia in 2022 until now, one of which is Lazada, aims to determine the influence of quality and promotion on Lazada E-commerce purchasing decisions in the city of Batam. This research uses SPSS which produces product quality and promotion variables have a significant positive effect along with Lazada E-commerce purchasing decisions in the city of Batam.